Faktor - Faktor yang Mempengaruhi Luas Pengungkapan Corporate Social Responsibility - Tista, Komang Rimba Rainugraha; Asri Dwija Putri, I G. A. M. (E-Jurnal Akuntansi, 2020)
Disclosure of corporate social responsibility becomes important for stakeholders to see whether the company has been responsible for the negative impacts arising from its activities. This research was conducted to empirically examine the effect of profitability, market capitalization, and public share ownership on the broad disclosure of corporate social responsibility of plantation companies listed on the Indonesia Stock Exchange 2014-2018. This research was conducted on all plantation companies listed on the Indonesia Stock Exchange 2014-2018. The number of observations obtained was 54 with a purposive sampling method. The analysis technique used is multiple linear regression analysis. Based on the results of the analysis found that profitability has a positive effect on ??CSR disclosure, market capitalization has a positive effect on ??CSR disclosure, and public share ownership has no effect on ??CSR disclosure. Keywords: Profitability; Market Capitalization; Public Share Ownership; Corporate Social Responsibility Disclosure.